Seismic Response Analysis of Shaft Tower Based on The Interaction of Soil-Well Bore-Shaft Tower. Issue 1 (December 2021) - Han, L T; Su, Y P; Chen, J W; Ge, N
Abstract: To study the influence of soil-well bore-shaft tower interaction on the seismic response of the shaft tower. A numerical analysis model of rigid foundation (without considering the interaction of soil-well bore-shaft tower ) and II site considering soil-well bore-shaft tower interaction is established by the finite element analysis method. The mode period, tower layer displacement and inter-story displacement of shaft tower are analyzed. The results show that, compared with rigid foundation, considering the interaction of soil-well bore-shaft tower, the mode period of the system is prolonged, the tower layer displacement and inter-story displacement of the shaft tower is enlarged. In the engineering design of shaft tower, the influence of the soil-well bore-shaft tower interaction on the seismic response of the shaft tower cannot be ignored.